1989
DOI: 10.1210/edrv-10-3-232
|View full text |Cite
|
Sign up to set email alerts
|

The Free Hormone Hypothesis: A Physiologically Based Mathematical Model*

Abstract: The free hormone hypothesis states that the biological activity of a given hormone is affected by its unbound (free) rather than protein-bound concentration in the plasma. The fundamental mathematical and physiological principles relating to this hypothesis are reviewed, along with experimental data that shed light on its validity. It is shown that whether or not this hypothesis is likely to be valid for any given hormone will depend largely on which step in the tissue uptake process (plasma flow, dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
462
4
15

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 873 publications
(505 citation statements)
references
References 0 publications
16
462
4
15
Order By: Relevance
“…However, in some conditions such parameter may not represent a reliable marker of vitamin D activity due to modifications of free hormone levels independently of total hormone storage and amount [8][9][10]. Consistently with the free hormone hypothesis, only hormone not bound to protein vectors can exert biological actions [11]. More than 80 % of circulating vitamin D (i.e., both 25(OH)-vitamin D and 1,25-dihydroxy-vitamin…”
mentioning
confidence: 94%
“…However, in some conditions such parameter may not represent a reliable marker of vitamin D activity due to modifications of free hormone levels independently of total hormone storage and amount [8][9][10]. Consistently with the free hormone hypothesis, only hormone not bound to protein vectors can exert biological actions [11]. More than 80 % of circulating vitamin D (i.e., both 25(OH)-vitamin D and 1,25-dihydroxy-vitamin…”
mentioning
confidence: 94%
“…Total CORT titers were reduced in handled kestrels, but the same was not true for free CORT because CBG capacity likewise was lower, resulting in similar free CORT levels in handled and non-handled birds. The free hormone hypothesis postulates that it is the unbound fraction of steroid hormones in the systemic circulation that is biologically active [48]. Following this argument, our data suggest that handling may not affect the ability of birds to mount appropriate adrenocortical responses, to the extent that an appropriate adrenocortical response is determined by levels of free CORT rather than total CORT.…”
Section: Possible Phenotypic Consequencesmentioning
confidence: 52%
“…One way that CBG may help regulate stress responsiveness is with its buffering capacity, explained by the "free hormone hypothesis." The free hormone hypothesis holds that only CORT that is not bound to a CBG molecule is "free" and accessible to target tissues and, thus, is biologically relevant [48]. According to this argument, modification of CBG levels alters the amount of free CORT that is available to target cells [7], even in the absence of changes in total corticosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol is commonly reported both as total cortisol and free cortisol. It is known that cortisol exists in plasma in three forms, 80-90% bound with high affinity to CBG, about 10-14 % associated with albumin and about 6-10% in unbound form as free cortisol [8,9,10,12,23,26,34,39,42]and it is suggested that only the free cortisol is biological active [8,10,12,36,42].There are several techniques for measurements and calculations of free cortisol but many of them are not suitable for routine laboratory use [5,11,12,15,17,43]. In this study we used a modified model (cortisol/CBG ratio) of the Free Cortisol Index [5].In our study we found no seasonal variations in the calculated cortisol-to-CBG ratio neither in OC users nor in non-users.…”
Section: Limitations and Methodological Aspectsmentioning
confidence: 99%